A novel deposition mechanism of Au on Ag nanostructures involving galvanic replacement and reduction reactions. Issue 67 (29th July 2021) - Xu, Juan; Yun, Qinru; Zhang, Han; Guo, Yanzhen; Ke, Shanlin; Wang, Jianfang; Zhu, Xingzhong; Kan, Caixia
Abstract : Au atoms originated from galvanic replacement reaction and reduction reaction would deposit at the surface energy-related facets and high curvature sites of Ag nanostructures, respectively, causing the final formation of Ag@Au nanostructures. Abstract : Combining a galvanic replacement reaction with a reduction reaction can provide more possibility in the synthesis of Au–Ag hollow nanostructures. However, the detailed atomic deposition mechanism involving these two reactions is unclear. Herein, we proposed a novel deposition mechanism of the Au atoms on Ag nanostructures involving simultaneous galvanic replacement and reduction reactions. The Au atoms originating from galvanic replacement reaction will deposit at surface energy-related facets of the Ag nanostructures while the others originated from reduction reaction at high curvature sites, with the morphology of the final Ag@Au nanostructures determined by the ratio between the two reactions. This mechanism has been verified by experiments on Ag nanorods using varied volumes of Au precursor. Moreover, it can also be extended to Ag cuboctahedrons, suggesting the generality of this mechanism.